Loss of the Drosophila melanogaster DEAD box protein Ddx1 leads to reduced size and aberrant gametogenesis - Germain, Devon R. (Dev Biol, 2015)
Mammalian DDX1 has been implicated in RNA trafficking, DNA double-strand break repair and RNA processing; however, little is known about its role during animal development. Here, we report phenotypes associated with a null Ddx1 (Ddx1(AX)) mutation generated in Drosophila melanogaster. Ddx1 null flies are viable but significantly smaller than control and Ddx1 heterozygous flies. Female Ddx1 null flies have reduced fertility with egg chambers undergoing autophagy, whereas males are sterile due to disrupted spermatogenesis. Comparative RNA sequencing of control and Ddx1 null third instars identified several transcripts affected by Ddx1 inactivation. One of these, Sirup mRNA, was previously shown to be overexpressed under starvation conditions and implicated in mitochondrial function. We demonstrate that Sirup is a direct binding target of Ddx1 and that Sirup mRNA is differentially spliced in the presence or absence of Ddx1. Combining Ddx1 null mutation with Sirup dsRNA-mediated knock-down causes epistatic lethality not observed in either single mutant. Our data suggest a role for Drosophila Ddx1 in stress-induced regulation of splicing.